Exploring Hatred in Angie Thomas’s The Hate U Give - Prasetya, Paramitha Indra; Prasaja, Yosep Bavo Agung (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This thesis analyses the portrayal of hatred in Angie Thomas’s The Hate U Give, focusing on its various forms, causes, and impacts. Hatred is a complex, deeply rooted emotion shaped by personal experiences and social influences. The writer uses a qualitative descriptive research design to identify and analyze the forms of hatred found in the novel. The text is interpreted in depth to explore the social and emotional meanings behind each representation of hatred, using a sociological approach because the novel portrays systemic injustices such as racism and economic exploitation. This thesis applies Gordon Allport’s theory of prejudice as the main theoretical framework, supported by several conceptual definitions. The theory of the definition of hatred explains that hate is a broad and focused emotion, marked by deep rejection of individuals, groups, or ideas, often with a desire to violate or erase the object. The theory of causative factors argues that hatred stems from ongoing social inequality and systemic discrimination. The theory of forms of hatred explains that emotional hatred often arises from painful personal experiences such as trauma, betrayal, or unfair treatment, which are internalized as chronic anger and resentment. The theory of relations between hatred explains that hatred is interconnected in a cycle that reinforces itself and impacts society broadly. In the digital era, personal, social, and institutional hatred interact dynamically and spread easily through social media. The theory of the impact of hatred states that hatred damages relationships between majority and minority groups, such as ethnic, religious, or national groups. This qualitative descriptive approach is strengthened with psychological and sociological perspectives to examine narrative elements, character dialogues, and plot developments depicting hatred in the novel. Data is collected through close reading and selecting relevant quotations, then analyzes based on the established theories. The study finds that hatred in the novel appears as racial, institutional, and embraced hatred, expressed explicitly, implicitly, and systemically. Contributing factors include societal stereotypes, media representation, and family or community dynamics. The impact of hatred is significant: it affects individuals’ psychological states (trauma, identity conflict, suppression), damages community relationships, and reinforces social divisions through institutional injustice.